Fetal cardiac Doppler changes in gestational diabetic pregnancies and its relationship with perinatal outcomes. Issue 10 (12th July 2021) - Özalp, Miraç; Demir, Omer; Dinç, Gülseren; Şal, Hidayet; Aran, Turhan; Osmanağaoğlu, Mehmet Armağan; Dilber, Embiya
Abstract: Aim: To examine the structural and functional changes of the fetal heart in gestational diabetes mellitus (GDM) and to evaluate the power of fetal cardiac Doppler parameters in predicting adverse perinatal outcomes in this group of pregnancy. Methods: Within the study's scope, 36 cases in the A1 GDM group, 33 cases in the A2 GDM group, and 124 cases in the control group were evaluated. The relationship between structural and functional fetal cardiac parameters and perinatal outcomes was evaluated via fetal echocardiography. Results: Fetal left ventricular myocardial performance index (MPI) values were found to be statistically significantly higher when compared between the A1 GDM and A2 GDM groups and the control group ( p = 0.000 and p = 0.000, respectively), while the E/A ratio was found to be significantly lower ( p = 0.000 and p = 0.000, respectively). It was determined that the maternal blood HbA1c level showed a significant negative correlation with the fetal cardiac E/A ratio and a significant positive correlation with isovolumetric relaxation time and MPI ( p = 0.000, p = 0.000, and p = 0.000, respectively). Adverse perinatal outcome rate was higher in the diabetic group (46.4%–22.6%). When the cases with GDM were examined in terms of perinatal outcomes, it was observed that there was a significant difference in HbA1c levels, E/A ratio, and MPI values between the cases in the group with adverse perinatal outcomes and the group with normal results ( p = 0.001, p = 0.000, and p = 0.000, respectively). Conclusions: The strong relationship between abnormal cardiac function and adverse perinatal outcomes suggest that cardiac Doppler may be a valuable tool for fetal monitoring and management for the GDM patient group.